Pengaruh Sarapan Terhadap Konsentrasi Belajar Siswa - Aisyatirradiyah, Syarifah; Samsul Hakim; Alfan Hadi (STAI AL-AMIN, 2024)
Irregular breakfast will have several negative impacts. Breakfast habits will affect learning concentration levels and successful learning requires optimal concentration for both teachers and students. This is because people with poor concentration have difficulty concentrating when listening, reading or writing. This study aims to analyse and examine whether there is an effect of breakfast on students‘ learning concentration in grade 1 of SDN 3 Bengkel, and how much influence breakfast has on students’ learning concentration in grade 1 of SDN 3 Bengkel. The research method used is Quantitative descriptive method. The population in this study were all grade 3 students of SDN 3 Bengkel, and the sample was 50% of the total population, namely 36 students. Data collection in this study was using questionnaires, interviews, and observations. The results of data processing were then carried out descriptive correlational analysis with the formula P = F / N x 100%, after which it was continued using the product moment formula. From the results of these calculations, it is concluded that there is a positive influence between breakfast on student learning concentration in class 1 SDN 3 Bengkel with a product moment correlation index number of 1.023. While the level of influence obtained from breakfast with learning concentration is 104.65%.